ESG Governance and Financial Performance: The Role of the Board in Integrating Sustainability into the Strategy of Indonesian Public Companies - Andrian, Yuni (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2024)
This study analyzes how the board's role (structure and process)drives the integration of environmental, social, and governance(ESG) into corporate strategy and its implications for the financialperformance of listed companies listed on the Indonesia StockExchange. Using a panel-based quantitative-empirical design(2019–2025), the study develops an auditable Strategic ESGIntegration Index (ESG-SI)—covering the linkage of ESG targets toplanning & budgeting, green capital allocation, ESG risk recordingin the risk register, ESG KPI linkage to executive remuneration, andassurance data. Key board variables include the proportion ofindependent commissioners, gender diversity, ESG expertise ofboard members, the existence of a sustainability/risk committee,the intensity of the ESG agenda, and board training. Therelationships are tested using panel regression (firm and year fixedeffects), mediation tests (SEM-PLS/bootstrapping), and robusttests (alternative performance proxies, winsorizing, and indexredefinition). The results show that board ESG expertise, theintensity of the ESG agenda, and the relevance of ESG KPIs toremuneration significantly enhance ESG-SI. Furthermore, ESG-SIis positively associated with ROA and lowers the cost of equitycapital (COE), with a stronger effect in high-ESG risk industries.These findings support a mediating mechanism: effective boards→ strategic ESG integration → improved financial performance.The study's key contributions are the clear distinction betweensymbolic disclosure and process-based strategic integration andresource allocation, the measurement of boardcompetencies/processes as drivers of integration, and newevidence from emerging market contexts. Practical implicationsinclude strengthening board ESG competencies, institutionalizingthe ESG agenda, and aligning remuneration with sustainabilitytargets, while policy implications encourage process- and outcomebaseddisclosure.